Reading Skills of Children with Dyslexia Improved Less Than Expected during the COVID-19 Lockdown in Italy - Ilaria Maria Carlotta Baschenis; Laura Farinotti; Elena Zavani; Serena Grumi; Patrizia Bernasconi; Enrica Rosso; Livio Provenzi; Renato Borgatti; Cristiano Termine; Matteo Chiappedi (Children, 2021)
Following school closures due to the SARS-CoV-2 pandemic, for some months, children received only distance learning. The effects of this approach, however, are not clear for children with dyslexia. We conducted a cross-sectional comparison between children with and without dyslexia after the so-called “lockdown” and a comparison between pre- and post-lockdown parameters in children with dyslexia. We recruited sixty-five children with dyslexia (dyslexia group, DG) from an outpatient facility in Pavia (Lombardy, Italy) and fifty-two children without specific learning disabilities as the control group (CG) from summer camps in the same province. We performed neuropsychological tests to explore reading skills and an ad hoc questionnaire to explore how parents and children had experienced the measures taken to reduce spreading of SARS-CoV-2 infection. Between 59 to 63% of children with dyslexia did not reach the average expected increase of reading skills. According to their parents, they also showed greater social isolation and fewer worries about the pandemic and the school’s closure. Our data indicate that children with dyslexia are at increased risk of consequences on their learning potential in case of school closure. They also seem to have a peculiar psychological experience of school closure. Specific interventions should therefore be provided to minimize the risk of negative effects on global development.